Bimodal crystallization at polymer–fullerene interfaces. Issue 3 (8th December 2014) - Môn, Dyfrig; Higgins, Anthony M.; James, David; Hampton, Mark; Macdonald, J. Emyr; Ward, Michael B.; Gutfreund, Philipp; Lilliu, Samuele; Rawle, Jonathan
Abstract : The growth-kinetics of PCBM crystals, on two different length-scales, is controlled by the thickness of the polymer layer within a PCBM–polymer bilayer. Abstract : The growth-kinetics of [6, 6]-phenyl C61-butyric acid methyl ester (PCBM) crystals, on two different length-scales, is shown to be controlled by the thickness of the polymer layer within a PCBM–polymer bilayer. Using a model amorphous polymer we present evidence, from in situ optical microscopy and grazing-incidence X-ray diffraction (GIXD), that an increased growth-rate of nanoscale crystals impedes the growth of micron-sized, needle-like PCBM crystals. A combination of neutron reflectivity and GIXD measurements, also allows us to observe the establishment of a liquid–liquid equilibrium composition-profile between the PCBM layer and a polymer-rich layer, before crystallization occurs. While the interfacial composition-profile is independent of polymer-film-thickness, the growth-rate of nanoscale PCBM crystals is significantly larger for thinner polymer films. A similar thickness-dependent behavior is observed for different molecular weights of entangled polymer. We suggest that the behavior may be related to enhanced local-polymer-chain-mobility in nanocomposite thin-films.